Profit-Sharing Practices in Catfish Farming: An Islamic Economic Law Analysis in South Sumatra Indonesia - Silvia Ayu Awalia; Relit Nur Edi; Juhratul Khulwah (UIN Siber Syekh Nurjati Cirebon, 2025)
This study analyzes profit-sharing practices in catfish farming in Srikaton Village, Buay Madang Timur District, East Ogan Komering Ulu Regency, South Sumatra, from the perspective of Islamic economic law. The main objective of this research is to examine the conformity of existing profit-sharing mechanisms with the principles of mudharabah as regulated in Islamic jurisprudence and sharia economic regulations. This research employs a qualitative field research approach using participatory observation, in-depth interviews, and document analysis. Data were collected from key informants consisting of capital owners, pond managers, and religious figures, and were analyzed using the Miles and Huberman interactive model. The findings indicate that profit-sharing practices in catfish farming are generally based on verbal agreements without written contracts, resulting in unclear contractual terms, limited cost transparency, and unilateral changes in profit-sharing ratios at the end of the production cycle. These practices do not fully comply with the fundamental principles of mudharabah, particularly contractual clarity, transparency (al-shafāfiyyah), and justice (al-‘adl). Changes in profit-sharing ratios without prior mutual consent potentially lead to injustice and undermine trust between the contracting parties. This study contributes to Islamic economic law by providing empirical evidence from the fisheries sector and highlighting the importance of formalized mudharabah contracts in rural economic activities. It recommends the implementation of written agreements, full cost transparency, and periodic review mechanisms to ensure fairness, legal certainty, and the sustainability of profit-sharing partnerships in accordance with sharia principles.Keywords: profit-sharing; catfish farming; Islamic economic law; mudharabah; transparency